Changes in feral dog populations during the COVID-19 pandemic in Arequipa, Peru - De la Puente-León, Micaela; Díaz, Elvis W.; Bellotti, Brinkley Raynor; Porras, Guillermo; Borrini-Mayorí, Katty; Chuquista-Alcarraz, Olimpia; Paz-Soldán, Valerie A.; Levy, Michael Z.; Castillo-Neyra, Ricardo (Frontiers in Veterinary Science, 2026)
BackgroundFeral dogs in Arequipa, Peru, inhabit caves in periurban areas and they may access and rely on organic waste from landfills and livestock from backyard farms. These feral dogs frequently attack small and medium farm animals and occasionally people, posing significant public health risks. Beyond the physical injuries resulting from the attacks, these dogs pose a threat for dog-mediated human rabies as there is active virus transmission in the dog population of Arequipa city. The COVID-19 pandemic restrictions in Arequipa, including restaurant closures, led to a decline in backyard farming and organic waste, thereby reducing food availability for feral dogs.MethodsWe longitudinally (2019–2022) examined the impact of pandemic restrictions on feral dog presence in the periurban areas of Arequipa. Monthly surveys recorded direct and indirect evidence of feral dog presence in caves. An interrupted time series (ITS) analysis evaluated changes in the number of caves with evidence of feral dogs before and after pandemic restrictions. In addition, we conducted in-depth interviews with local farmers to understand the interactions and conflicts between feral dogs and human populations in those periods.ResultsOver 29 months (7 pre-pandemic, 22 during/post-pandemic), an average of 16.42 caves per month showed evidence of feral dog presence, mostly in the form of indirect evidence. Following the pandemic restrictions, the total number of occupied caves decreased by 42% (p < 0.010), with a 41% reduction in indirect evidence (p = 0.012) and a striking 76% decrease in direct evidence of feral dogs (p < 0.001). Farmers described an initial increase in dog attacks immediately following the onset of restrictions, followed by an overall decline as feral dog numbers decreased.ConclusionThe observed population decline suggests that reduced food availability impacted the local feral dog population. The greater reduction in direct evidence compared to indirect signs indicates a decline in active feral dog presence. These findings describe shifts in feral dog population dynamics during the period of COVID-19 restrictions. The factors driving these changes remain uncertain and could include mortality, migration, or altered behavior. Understanding how food availability and other environmental conditions influence these dynamics is essential for designing interventions that minimize unintended consequences of disease transmission and animal welfare.